Contribution Of Leadership And Environmental Work In Improving Employee Motivation - Sulistyan, Riza Bahtiar (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2017)
Employee motivation is important for a district office and is used to measure the success of the leadership and work environment in improving employee motivation. This study aims to determine and analyze employee perceptions of leadership and work environment in improving employee motivation. Respondents in this study are civil servants in the District office in Lumajang Regency totaling 78 people. Data analysis used is instrument test which includes validity and reliability test, classical assumption test include data normality test, multicollinearity test and heteroscedasticity test. Then multiple linear regression analysis and hypothesis test. As an independent variable that is leadership and work environment, and the dependent variable is motivation. From the hypothesis test concluded that the two hypotheses that have been built are rejected. The results showed that the leadership perceived employees have no significant effect in improving motivation, meaning there is no important effect of leadership in increasing motivation. The employee's perceived work environment has no significant effect on improving motivation, meaning that the work environment does not have an important effect in increasing motivation. Based on the findings, leadership needs to get attention in improving employee motivation